Agroecological business model diagnostics and upgrading plan for sorghum contract farming in Mbire Dstrict, Zimbabwe - Zingwena, Taurai; Debello, Moti Jaleta; Ngoma, Hambulo; Dorcas, Matangi; Chimonyo, Vimbayi G.P.; Dawes, Michael; Mushongachiware, Rodney (CGIAR, 2024)
This report synthesizes the processes followed to identify potential agroecology business models, the business model diagnostics, financial and viability analyses conducted, and business support and upgrading for a Sorghum contract farming out-grower scheme in Mbire District in Zimbabwe. Centered on agroecological principles, the report synthesizes findings from the Value Chain Analysis, Business Model Canvas, and Agroecology assessments, alongside a SWOT analysis and lessons from implementation challenges. Key findings from the existing business model revealed partial alignment with agroecological principles, achieving a B-ACT score of 52%, highlighting significant room for improvement in biodiversity, resource efficiency, and social equity. The SWOT analysis underscored strengths like high demand for drought-tolerant sorghum and robust market linkages. However, weaknesses include dependency on rainfed agriculture and limited access to financial and technical resources. Challenges such as climate variability, especially drought, and gaps in participatory governance emerged as critical barriers to success. To address these, there is a need to deepen agroecological integration by promoting crop diversification, organic inputs, and synergies between crop and livestock systems, reducing environmental impact while enhancing resilience; and strengthening farmer capacity through participatory training in Integrated Pest Management (IPM) and conservation practices, alongside embedding indigenous knowledge systems. Moreover, financial accessibility should be improved through climate-resilient financial products and market innovations like price stabilization mechanisms. Investments in infrastructure, including irrigation and processing facilities, are vital for reducing climate vulnerabilities and post-harvest losses. By implementing these strategies, the model can transform into a scalable, resilient framework for agroecological and economic progress.